2019
DOI: 10.1590/fst.02618
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the texture and retrogradation properties of Niangao (Rice Cake) made with naturally fermented rice flour

Abstract: Niangao is prepared from polished round-grained or waxy rice flour and it is a popular and traditional steamed rice cake in China, but its preparation is different. On this study, Niangao was produced with naturally fermented rice flour and the effects of fermentation on physical properties and rheological characteristics were investigated. The results suggest that the water-holding capacity, texture, and color of the samples were significantly improved after natural fermentation, while amylose content was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…They showed versatile pasting properties reflecting the difference in cultivars, locations, and climate conditions. In our previous study [ 28 ], the pasting properties of 38 rice samples were measured using an RVA, by which we developed novel estimation formulae for estimating apparent amylose content (AAC) and resistant starch (RS). Using the same estimation formulae, we estimated AAC and RS values and these are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed versatile pasting properties reflecting the difference in cultivars, locations, and climate conditions. In our previous study [ 28 ], the pasting properties of 38 rice samples were measured using an RVA, by which we developed novel estimation formulae for estimating apparent amylose content (AAC) and resistant starch (RS). Using the same estimation formulae, we estimated AAC and RS values and these are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the consumption of rice at home has been decreasing, and the consumption of rice from take-out lunch-boxes and rice dishes served at restaurants has been increasing in Japan, Korea, and China [ 28 ]. In such cases, the quality of the cooked rice is evaluated not only just after cooking but also several hours after cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on development of gluten free cake is studied extensively in the literature. Feng et al (2019) prepared rice cake with naturally fermented rice flour. Türker et al (2016) investigated the effect of green banana peel flour substitution on physical properties of gluten free cakes.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the small clusters of starch chains or molecules that could be easily dissociated, hydrated, and swollen during gelatinization with excess water, thus contributing to an increase in pasting viscosity [23]. Tester and Morrison reported that swelling of starch granules was inhibited by complexes formed with amylose and lipids which results in a lower peak viscosity, the complexes could significantly affect the texture of products [24]. Final viscosity is the amount of recovery of starch viscosity during cooling of the reheated starch pastes and is thus usually related to the amylose content of starch.…”
Section: Slr Statisticmentioning
confidence: 99%